Superficial Temporal Artery and Vein as Alternative Recipient Vessels for Intraoral Reconstruction With Free Flaps to Avoid the Cervical Approach With the Resulting Need for Double Flap Transfer in Previously Treated Necks - Ritschl, Lucas M.; Niu, Minli; Pippich, Katharina; Schuh, Philia; Rommel, Niklas; Fichter, Andreas M.; Wolff, Klaus-Dietrich; Weitz, Jochen (Frontiers in Oncology, 2022)
Background Microvascular reconstruction remains challenging in previously operated and irradiated patients, especially when double flaps seem to be the only solution due to osteoradionecrosis. An alternative reconstructive option could be microvascular anastomosis to the temporal vessels to avoid the obligatory cervical incision. Methods and Materials All consecutive cases between January 2013 and 2020 that underwent either mandibular resection and reconstruction with a free fibula flap (FFF) and another soft tissue flap (group I) or pure intraoral resection and reconstruction with an FFF or radial forearm flap (RFF) with temporal microvascular anastomosis (group II) were included. Patients’ general information, indication and extent of surgery, time of ischemia, time of total surgery, and duration of hospital stay as well as incidence of complications were retrospectively recorded and analyzed. Results Seventeen (group I) and 11 (group II) cases were included. In group I, FFF was combined with RFF (n = 9), anterolateral thigh flap (ALT, n = 7), or latissimus dorsi flap (n = 1). Group II consisted of six FFFs and five RFFs. Operation time and hospitalization duration were significantly shorter in group II (p < 0.001 and p = 0.025), whereas ischemic time of FFF was significantly shorter in group I (p = 0.002). All patients in group I required a tracheostomy, while only four cases in group II did (p = 0.004). The complication rate regarding hematoma removal, revision of anastomosis, flap loss, delirium, sepsis, pleural effusion, pneumonia, and pulmonary artery embolism showed no significant differences between the two groups. Conclusions The superficial temporal vessels served as versatile recipient vessels for intraoral mandibular and soft tissue reconstruction and led to reduced operation time, hospitalization duration, and indication for a primary tracheostomy. Thus, this approach may help to avoid cervical incision for reconstruction in irradiated patients.